Relação entre padrão de sono e obesidade em mulheres com fibromialgia - Araújo, Tânia Aparecida de (2014)
Fibromyalgia (FM) is characterized by painful body regions, non-restorative sleep, fatigue, mood disturbances and depression. Evidence has shown that FM is closely associated with overweight and obesity development. In addition, sleep disorders which include frequent awakenings, daytime sleepiness, shorter duration and sleep efficiency are frequent and highly uncomfortable in these patients. At present, the relationship between the occurrence of overweight and obesity and the sleep pattern is poorly described in the literature. The objective of the present study was to investigate the relationship between obesity and sleep pattern in women with FM. Participated in the study a total of 100 adult female patients with a prior medical diagnosis of fibromyalgia. Body mass, height (to calculate body mass index) were assessed, besides the measurement of waist circumference. The diet quality was evaluated using a 24-hour dietary recall with subsequent determination of the Healthy Eating Index (AHEI). Subjective analyses of daytime sleepiness (Epworth Sleepiness Scale) and sleep quality (Pittsburgh Sleep Quality) were performed. The results demonstrate an obesity rate of 41% of all women studied (56.1% were sleepy and 43.9% weren t sleepy, p=0.04). Obese women showed a greater level of sleepiness when compared with non-obese (10.2 and 7.0, respectively; p=0.004), but no there were no differences in relation to sleep time (6.9 and 6.6, respectively, p=0.41) and sleep quality (12.5 and 12.6, respectively, p=0.94). Sleepy women showed a greater weight gain after the diagnosis of fibromyalgia when compared with nonsleepy women (11.7 kg and 6.4kg, respectively; p=0.04). A positive and significant correlation between BMI and sleepiness (r=0.35, p=0.02) was also found. In multivariate logistic regression, moderate or severe sleepiness (ESS >12) was associated with obesity (odds ratio=3.44, 95% confidence interval: 1.31-9.01, p=0.04). These results demonstrate an important association between sleepiness and FM, suggesting that the occurrence of obesity may be involved with sleepiness in these patients.